Analisis Struktur Beton Pelat Lantai dan Balok dengan Metode Bekisting Sistem Fix Shoring - Arisyi, Luthfan; Dewita, Hikma; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
In the construction of a building, it is necessary to plan a concrete structure that can make us feel safe and comfortable. The concrete structure itself is very close to making a slab and beam, the design and implementation of a slab and beam has many innovations in the manufacturing process. One of the information during the construction of the structure is formwork with a fixed shoring system. Where when the formwork can be removed quickly enough from the usual time, this will cause a reaction on the structure itself and the fix shoring is the part that reduces the impact of the reaction. The purpose of this study was conducted to find out whether the fix shoring system formwork is able to provide safe results according to the building permit. The fix shoring method based on the results of the analysis obtained, the floor slab concrete structure was able to withstand the deflection that occurred on day 2 (2.891 of the maximum deflection of 8.333). Meanwhile, the elastic deflection only met the requirements on day 3 (Mu<Mcr, 8.729 kN/m < 8.700 kN/m). For the concrete structure itself has a size of 40x70 and 30x70. The conclusion is that the overall results comply with the specified permits from the pedestal to the field. It can be stated that the formwork of the fixed shoring system, on the 3rd day, the formwork can be removed without affecting the state of the concrete structure.